Penipuan Dalam Jual Beli Online: Perspektif Hukum Telematika - Muhammad Kamran; Maskun Maskun (Fakultas Hukum Universitas Pattimura, 2021)
Introductioan: The current proliferation of online buying and selling is also followed by the high risk of online fraud.Purposes of the Research: Know and understand the legal effects of fraud in online buying and selling agreements in the Indonesian positive law.Methods of the Research: This research is a normative legal research. It applied some approaches such as a statutory approach, a case approach, a conceptual approach, an analytical approach, and a theoretical approach. The legal materials used were qualified as a primary, secondary, and tertiary legal materials. They were then analysed with qualitatively with deductive and inductive methods.Results of the Research: The legal consequence of fraud in online buying and selling agreements in the Indonesian positive law creates responsibility for consumer losses in electronic transactions as regulated by those regulations. For losses of the consumer, the person, who due to his/her fault published the loss, should compensate the loss.